Korean War almanac - Edwards, Paul M. (Facts On File, 2006)
Alphabetically arranged entries bring the period to life by vividly describing the people, types of weaponry employed, and many other interesting details relevant to this study
Includes bibliographical references and index
Keywords: Nations Unies - Forces armées - Corée; Vereinte Nationen; United Nations -- Armed Forces -- Korea; Guerre de Corée, 1950-1953; Guerre de Corée, 1950-1953 - Chronologie; Guerre de Corée, 1950-1953 - États-Unis; Korean War, 1950-1953 -- Chronology; Korean War, 1950-1953; Korean War, 1950-1953 -- United States; Koreakrieg; USA